WHAT MATTERS MOST FOR LECTURER PRODUCTIVITY? ASSESSING THE RELATIVE CONTRIBUTIONS OF COMPETENCE, MOTIVATION, AND WELL-BEING IN PRIVATE HIGHER EDUCATION - Hary Murcahyanto; Hartini Haritani (Nurul Jadid University, 2026)
Improving instructional quality, research performance, and institutional competitiveness has made lecturer productivity a key priority for higher education institutions. Although competence, motivation, and well-being are widely recognized as important determinants of academic performance, these factors are often examined separately, particularly in private universities. This study investigates the influence of competence, motivation, and well-being on lecturer productivity in private universities in West Nusa Tenggara, Eastern Indonesia. Using a quantitative explanatory design with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 39 purposively selected lecturers. The findings indicate that competence is the strongest predictor of lecturer productivity, followed by motivation, while well-being has a relatively smaller influence. The proposed model explains 48.1% of the variance in lecturer productivity, indicating moderate explanatory power. By integrating these three factors into a single analytical model, this study provides empirical evidence from an underrepresented higher education context. According to the findings, lecturer productivity should be focused on competency growth and motivation and well-being should be strengthened to maintain academic success.